Zarządzanie personelem w jednostce badawczo-rozwojowe - Tkaczyk, Stanisław (Personnel Management in a Research and Development Unit, 2008)
In the study, a process of managing staff of a Research and Development Unit (JBR) has been described. Such units, apart from a fully fledged institutes, represent one of the main sources of knowledge-based services. It has been underscored that this peculiar type of a research and development entity requires particular way of personnel management, characterized by high scientific and professional standing, working in a turbulent environment (especially exterior one) and directed versus gaining a competition edge on this complex research market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 575-583